1993
DOI: 10.1038/sc.1993.57
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric wheelchair athletics: sports injuries and prevention

Abstract: Two hundred and forty-seven competitors at the 1990 Junior National Wheel chair Games (USA) were surveyed for general information, training techniques, and injury patterns. Eighty-three athletes (34%) responded to the retrospective survey. Injuries were reported by 97% of those participating in track, 22% of the field participants, and 91% of the swimming competitors. A wide variety of injuries was reported ranging from minor bruises, blisters and abrasions to more serious problems (bladder infections, hyperth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In contrast, the only previous study of sports injuries among athletes with a disability reported that 97% of elite youth wheelchair athletes with disabilities were injured annually. 6 A higher intensity of practice and competition among elite athletes who participate in a national league is not surprising and likely leads to greater injury risk compared with athletes from an interscholastic program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the only previous study of sports injuries among athletes with a disability reported that 97% of elite youth wheelchair athletes with disabilities were injured annually. 6 A higher intensity of practice and competition among elite athletes who participate in a national league is not surprising and likely leads to greater injury risk compared with athletes from an interscholastic program.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-seven percent of 6-to 18-year-old wheelchair athletes from the junior division of the National Wheelchair Athletic Association reported an injury either during training or competition in 1990. 6 To address this research gap, our study examined injury during organized competitive sports in the special education school setting. Eight teams were followed for 4 sports seasons from a special education interscholastic sports league in a large urban school district.…”
mentioning
confidence: 99%
“…Our report also includes several adaptive sports that have been less well studied even at the elite level. Sports most commonly studied in the literature include wheelchair basketball, track and field, swimming, and wheelchair racing . There have been very few studies investigating injuries incurred in adaptive rowing, wheelchair rugby, and sled hockey .…”
Section: Discussionmentioning
confidence: 99%
“…In general, athletes with myelomeningocele have decreased aerobic power and, decreased peak anaerobic power (1,3,4,14). There is also a high association of Arnold-Chiari type 2 malformations and tethered cord syndrome in these adolescents.…”
Section: Myelomeningocelementioning
confidence: 99%
“…Athletes participating in wheelchair athletics are at a higher risk for upper extremity overuse injuries, shoulder and wrist being the most common injuries reported (13,14). Athletes participating in wheelchair athletics are at a higher risk for upper extremity overuse injuries, shoulder and wrist being the most common injuries reported (13,14).…”
Section: Wheelchair Athletesmentioning
confidence: 99%